Giant Adult Mesenteric Lipoma: A Rare Cause of Chronic Abdominal Distention and Discomfort - Houssam Khodor Abtar; Fahed Kheireddine Abdallah; Rayan Said Lakkis; Jad Jamal Terro; Nathalie Haidar Ismail; Mohammad Ahmad Al Raishouni; Houssein Haidar Ahmad; Kassem Mohammad Jammoul (Case Reports in Surgery)
Solitary or multiple lipomas are considered common tumors that can occur anywhere in the body; however, mesenteric lipoma is a rare entity that is well known to present with signs and symptoms of small bowel volvulus. Hereby, we present a case of a 54-year-old male patient with multiple comorbidities who was suffering from chronic abdominal discomfort and gradual increase of his abdominal distention over many years without seeking any medical attention. The patient was seen by a general practitioner after complaining of an inflated abdomen, as he described his condition. After several imaging studies, he was diagnosed with one of the largest mesenteric lipomas in the literature. Mesenteric lipoma should be present in the differential diagnosis of any abdominal tumor. Magnetic resonance imaging plays a major role in differentiating benign from malignant lipomas.